Overcoming Poverty and Social Inequality in Third World Countries (Latin America, Africa) - Балджи, Марина Дмитрівна; Baldzhy, Maryna D.; Drobotya, Yana; Pecheniuk, Alla; Savelchuk, Iryna; Hryhorenko, Dmytro; Kulinich, Tetiana (My University, 2021)
The relevance of the research is due to the fact that the issue of poverty is one of the most acute social problems of the beginning of the third millennium. The phenomenon of poverty is widespread in third world countries as well as it is observed in relatively developed countries. Poverty rates in Latin America are threatening. Consequently, the issue of social and economic inequality in these countries has become extremely acute. The purpose of the research: to identify the causes of poverty and social inequality and substantiate the main directions of poverty reduction in third world countries. The research methods: comparative analysis; index method; systematization; grouping; generalization. Results. The classification of the causes of poverty has been carried out and the directions of its overcoming in the countries of Latin America on groups of indicators have been defined, namely: 1) political; 2) economic; 3) demographic; 4) regional-geographical; 5) social; 6) qualification; 7) personal. Based on the Net Domestic Product indicator, a comparison of economic indicators of the studied countries has been carried out. It has been revealed that from 1990 to 2018 income inequality increased in 52 of 119 countries studied, and decreased in 57 states. Inequality has increased in the world’s most populous countries, particularly China and India. In general, countries with growing inequality are home to more than two-thirds (71%) of the world’s population. Trends in the distribution of income in the world have been investigated by applying the Gini index, the high level of which is observed in Latin America (Colombia 48,9%, Panama 46,1%, Chile and Mexico 45,9%). The forecast of the impact of the Covid-19 pandemic on this issue has been outlined; the ways of its impact on the economies of the countries have been studied. As a result of the study, the main directions and mechanisms of the strategy for poverty reduction and social inequality in the third world countries have been identified. The implementation of the poverty reduction strategy presented in this academic paper may have a positive impact on the economic situation of the population of Latin American countries
Overcoming Poverty and Social Inequality in Third World Countries (Latin America, Africa) / Y. Drobotya, M. Baldzhy, A. Pecheniuk, I. Savelchuk, D. Hryhorenko, T. Kulinich // International Journal of Computer Science and Network Security. – 2021. – Vol. 21, № 3. – Р. 295-303. https://doi.org/10.22937/IJCSNS.2021.21.3.38
Keywords: Poverty; Social Inequality; Poverty Reduction; Income Poverty Line; Income Distribution; Research Subject Categories::SOCIAL SCIENCES